2000
DOI: 10.1103/physrevb.62.11118
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling spectra of impurities in the Fe(001) surface

Abstract: We present ab initio calculations of scanning tunneling spectra for the Fe͑001͒ surface and for 3d impurities in this surface. The calculations are performed by the full-potential Korringa-Kohn-Rostoker Green's-function method, and also partly by the full-potential linearized augmented-plane-wave method. For the clean Fe͑001͒ surface we demonstrate that the correct tunneling spectrum is only obtained in a full potential treatment, while the atomic-sphere approximation yields incorrect results. For 3d impuritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Davis et al 8 have observed similar localized states in STS measurements for Cr atoms in the surface layer of the Fe͑001͒ surface. Ab initio calculations of Papanikolaou et al 9 confirmed this and showed that similar localized states occur for many other impurities in the Fe͑001͒ surface.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Davis et al 8 have observed similar localized states in STS measurements for Cr atoms in the surface layer of the Fe͑001͒ surface. Ab initio calculations of Papanikolaou et al 9 confirmed this and showed that similar localized states occur for many other impurities in the Fe͑001͒ surface.…”
Section: Introductionsupporting
confidence: 62%
“…Since the states with k ʈ = 0 show no in-plane oscillations and exhibit the full symmetry of the surface, we find that for the ͑111͒ surface states with s, p z , and d z 2 show a slow decay in the vacuum region and can be well seen in STM, while other p and d states are strongly attenuated. An analogous argument holds for single adatoms on the ͑111͒ surface, since only these states exhibit the full point symmetry of the adatom-on-surface configuration, 9 and have thus no oscillations to use as a part of the kinetic energy.…”
Section: B 3d Impurities As Adatomsmentioning
confidence: 99%
“…For the impurity calculations we perform the self-consistent calculations for NiCrSi and produce the Green function for the bulk compound. 75,76 Then we consider a cluster of 65 atoms surrounding the Si site embedded in an infinite NiCrSi bulk crystal and calculate the electronic structure of the atoms in this cluster in real space considering a Cr atom at the central Si site. (We have to note here that we have neglected the relaxation of the atomic positions within the cluster due to the impurity atom, which is very tedious computationally, since we expect them to be small due to the high symmetry of the crystal and an extensive study of impurities is out of the scope of the present manuscript.)…”
Section: A Defects Conserving the Half-metallicitymentioning
confidence: 99%
“…Moreover Dyson equation makes possible the study of single impurities within the framework of FSKKR in real space. 75,76 In both cases we employed the local-spin-density approximation (LSDA) 77 for the exchange-correlation energy within the framework of the density functional theory. 78,79 Semi-Heusler alloys (also known as half-Heusler compounds) crystallize in the C1 b structure which consists of four fcc sublattices and have the chemical formula XYZ where X a high-valent transition metal atom, Y a lowvalent transition metal atom and Z a sp atom.…”
Section: Description Of Present Calculationsmentioning
confidence: 99%
“…Thus, for the Fe(I) atom the majority-spin DOS is reduced at the Fermi energy while the minority-spin DOS is enhanced and there develops a sharp peak just above the Fermi level. These interface states are analog with the Fe (0 0 1) surface states [15] and have been observed for many other barriers such as MgO [5,16], Ge [17], GaAs [17][18][19] and ZnSe [18]. On the barrier side, iron-induced interfacial states may be observed in the NaCl band gap (Fig.…”
Section: Fe Na CLmentioning
confidence: 88%